The gender bias in fundamental motor skills tests: A new agenda needed! - Okely, A.; Wright, J.
A child's level of fundamental motor skill (FMS) proficiency has been suggested as a precursor to their level of participation in sports, games, and physical activity throughout life. With this in mind there is a need to ensure adequate skill development is taking place in our schools. Resources have been developed to aid educators in the assessment, planning, implementation, and evaluation of FMS programs, but there appears to be a gender bias towards boys in the selection of the tests currently receiving prominence in Australia. Most batteries are strongly related to the skills integral to traditional male sports but are less associated with those which are essential to female activities. From these tests it is incorrectly deduced that girls are poorly skilled, when in reality they may be no less skilled than boys, but rather skilled in different areas. Tests are needed that assess components integral to popular female activities, to ensure an accurate indication of their skill level can be accomplished. An example of some tests will be considered, in an attempt to improve educational practices and stress the need for new methodologies for new times to be implemented.